Accidents in childhood: Casuistry of a tertiary service in a medium-sized city in Brazil - Gonçalves, Anderson César [UNESP]; Araújo, Maria Paula Bortoleti de [UNESP]; Paiva, Karina Veronezi de [UNESP]; Menezes, Caio de Souza Araújo [UNESP]; Silva, Anna Érica Mero Cavalcanti da [UNESP]; Santana, Giuliana de Oliveira [UNESP]; Ortolan, Erika Veruska Paiva [UNESP]; Lourenção, Pedro Luiz Toledo de Arruda [UNESP] (FapUNIFESP (SciELO), 2019)
Objective: to investigate the main causes and most common risk situations related to childhood accidents, in our local reality. Methods: an observational, cross-sectional, retrospective, descriptive, and analytical study from the medical records of patients attended in the pediatric emergency services of the hospital complex of Hospital das Clínicas, Botucatu Medical School-UNESP, in 2016. We included patients from zero to 15 years old who had received medical care related to accidents, determining age, gender, type of accident, period of the day, accident place, and history of previous accidents. Results: considering all consultations with appropriate medical records, 936 (27.5%) were related to accidents: 588 (62.8%) in male patients and 348 (37.2%) in female patients. As to age, 490 (52.3%) happened with children from zero to five years, 245 (26.2%) with children from six to ten years, and 201 (21.5%) with children over ten years. Falls and local traumas were the most common types of accidents in all analyzed age groups. Most accidents occurred in the afternoon (46.1%), at home (60.7%), and 26.6% of the patients had a history of previous accidents. Conclusion: accidents were responsible for a large portion of urgent care. The high rate of patients with previous accident records indicated the repeated exposure of these children to risk situations.
Acidentes na infância: Casuística de um serviço terciário em uma cidade de médio porte do Brasil
Keywords: Accident prevention; Child health; Health services research; Prevention & control